THE SIGNIFICANCE OF IMPROVISATION IN THE ETHNOGRAPHIC TYPE DANCES. A SHORT CASE STUDY: THE "CĂLUŞ" - Silvestru PETAC (Studia Universitatis Babeş-Bolyai. Musica, 2015)
Improvisation is one of the essential choreutic processes for the folkloric nature of traditional dances, therefore it should be accorded the same importance in the dances of ethnographic type, as elements of a sustainable safeguarding. After a relatively consistent bibliographical introduction, centered on one of the studies based most on the Romanian choreic data, this article puts forward a short case study focusing on the ways improvisation reveals itself along the dances integrated in the ritual of Căluş. Detecting the mechanisms of the improvisation at the levels of its choreic texts and co-texts aims to reveal the significance of this process throughout the re-folklorization of the dances of ethnographic type.